OS 12-03 SGLT-2-INHIBITION WITH DAPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT. (September 2016) - Schmieder, Roland; Ott, Christian; Linz, Peter; Jumar, Agnes; Friedrich, Stefanie; Titze, Jens; Hammon, Matthias; Uder, Michael; Kistner, Iris
Abstract : Objective: Sodium tissue content by 23 Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and, in parallel, of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes leads to decreased tissue sodium content due to its pharmacological action. Design and Method: In a prospective, double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to dapagliflozin 10 mg o.d. and placebo for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analyzed the sodium content in the skin and muscles of the lower leg by the Na-MRI at baseline, after the first and second treatment phase of 6 weeks. Results: Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11, p = 0.010) and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024) 24-hour ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline (24.1 ± 6.6 vs.22.7 ± 6.4 mmol/L; p = 0.013). No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 mmol/L, p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline. Conclusions: SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in sodium tissue content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes known to be salt sensitive and prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition.